2010
DOI: 10.1007/s00246-010-9783-9
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculocoronary Artery Connections With the Hypoplastic Left Heart: A 4-year Prospective Study: Incidence, Echocardiographic and Clinical Features

Abstract: Ventriculocoronary connections (VCCs), also called sinusoids, occur with hypoplastic left heart (HLH). Previous reports are limited to case reports, pathologic series, and surgical series with limited detail, which may underestimate the incidence and overestimate the severity of VCCs in HLH. A study was conducted to determine the incidence VCCs in HLH, their effect on survival, and their echocardiographic and clinical features. The echocardiograms and medical records of 100 consecutive neonatal HLH cases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 23 publications
0
31
0
1
Order By: Relevance
“…Vida and colleagues [1] found a 50% failure rate for stage I palliation in patients with this anatomic variant and Sathanandam and colleagues [2] suggested that large VCCs were associated with a poor prognosis. Although the exact mechanism for the increased mortality in this disease subtype remains unclear, some authors have proposed that the VCCs might interfere with adequate myocardial protection during heart decompression on CPB, resulting in ischemia-induced ventricular dysfunction [1,3].…”
Section: Commentmentioning
confidence: 97%
See 2 more Smart Citations
“…Vida and colleagues [1] found a 50% failure rate for stage I palliation in patients with this anatomic variant and Sathanandam and colleagues [2] suggested that large VCCs were associated with a poor prognosis. Although the exact mechanism for the increased mortality in this disease subtype remains unclear, some authors have proposed that the VCCs might interfere with adequate myocardial protection during heart decompression on CPB, resulting in ischemia-induced ventricular dysfunction [1,3].…”
Section: Commentmentioning
confidence: 97%
“…The ventricular condition could be visually confirmed during the procedure, and a postoperative echocardiogram showed preserved ventricular function. This technique is considered an effective option for minimizing myocardial damage in this patient subtype.(Ann Thorac Surg 2014;98:e103-5) Ó 2014 by The Society of Thoracic Surgeons V entriculocoronary connections (VCCs), also called ventriculocoronary fistulas or sinusoids, are frequently seen in patients with the mitral stenosis-aortic atresia (MS-AA) subtype of hypoplastic left heart syndrome (HLHS) [1,2]. The presence of VCCs is a risk factor for early failure after stage I palliation [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators 10 have reported a diminished survival rate of only 79% for patients with mitral stenosis with aortic atresia compared with the other subtypes for stage I Norwood palliation. Furthermore, recent studies [10][11][12] have indicated that HLHS with mitral stenosis and aortic atresia is associated with ventriculocoronary connections (sinusoids), which adversely affect outcomes and survival. HLHS with an intact or highly restrictive atrial septum is associated with extremely poor outcomes, with a survival rate of only 68% to 70% before discharge from the hospital after the Norwood procedure for patients deemed to be surgical candidates.…”
Section: Perinatal Factors That Affect Preoperative Managementmentioning
confidence: 99%
“…describe in detail the histopathologic characteristics of the ventriculocoronary connections that occur in the setting of ventricular hypoplasia. Historically, these connections have been described by a variety of terms used interchangeably (e.g., coronary artery fistulas, myocardial sinusoidal‐coronary arterial connections, ventriculocoronary connections, and myocardial sinusoids) . While coronary‐cameral fistulas have been encountered in the setting of an isolated atrial septal defect (ASD), VSD, or TOF, it is possible that the VCACs encountered in the setting of a hypertensive and hypoplastic ventricle represent an etiologically, histopathologically, and prognostically discrete subtype of fistulous connections, separate even from myocardial sinusoids …”
Section: Specific Anatomic Considerationsmentioning
confidence: 99%